2022
DOI: 10.3390/nu14040885
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection of Caffeinated Coffee-Induced Short-Term Effects on ECG Signals Using EMD, DWT, and WPD

Abstract: The effect of coffee (caffeinated) on electro-cardiac activity is not yet sufficiently researched. In the current study, the occurrence of coffee-induced short-term changes in electrocardiogram (ECG) signals was examined. Further, a machine learning model that can efficiently detect coffee-induced alterations in cardiac activity is proposed. The ECG signals were decomposed using three different joint time–frequency decomposition methods: empirical mode decomposition, discrete wavelet transforms, and wavelet pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…First, a superficial analysis of the accuracy curves shows that the amplitude of the classifiers' performance is within the expected range. The ability to detect physiological changes induced by caffeine demonstrates the discriminative power of ECG signals across both active and placebo modalities, highlighting the effectiveness of the DWT approach as documented in the literature [ 73 ]. Although the data extracted from these signals confirm that caffeine influences cardiac activity, the results do not precisely delineate the exact morphological changes in the ECG characteristics.…”
Section: Resultsmentioning
confidence: 95%
“…First, a superficial analysis of the accuracy curves shows that the amplitude of the classifiers' performance is within the expected range. The ability to detect physiological changes induced by caffeine demonstrates the discriminative power of ECG signals across both active and placebo modalities, highlighting the effectiveness of the DWT approach as documented in the literature [ 73 ]. Although the data extracted from these signals confirm that caffeine influences cardiac activity, the results do not precisely delineate the exact morphological changes in the ECG characteristics.…”
Section: Resultsmentioning
confidence: 95%
“…Pradhan and Pal (2020) have reported that it is possible to use time-domain statistical and entropy-based features extracted from the ECG signal to automatically detect the presence of a psychoactive drug, "cafeine," in the body [186]. In a recent study [187], the authors employed three diferent time-frequency methods, EMD, DWT, and WPD, to automatically detect the cafeinated cofee-inducedshort-term efect in the ECG signal. Te application of ECG signals in seeing the impact of drugs and alcohol is new, and hence, a limited study is available in the literature.…”
Section: Driver Distraction Detectionmentioning
confidence: 99%
“…Caffeine counteracts the effects of adenosine, and moderate doses (40-200 mg) increase alertness, reduce fatigue, and shorten reaction time (Ballis 2019;Dam et al 2020). Adenosine is a vasodilator, and its inhibition causes sympathetic reflexes to be activated (Pradhan et al 2022). Caffeine works by blocking adenosine receptors A1 and A2, as well as influencing the autonomic nervous system (ANS), preventing adenosis, which results in central nervous system (CNS) activity via catecholamine release (Pradhan et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine is a vasodilator, and its inhibition causes sympathetic reflexes to be activated (Pradhan et al 2022). Caffeine works by blocking adenosine receptors A1 and A2, as well as influencing the autonomic nervous system (ANS), preventing adenosis, which results in central nervous system (CNS) activity via catecholamine release (Pradhan et al 2022). Caffeine has an anti-obesity effect because it suppresses appetite, improves energy balance, basal metabolic rate, and thermogenesis by enhancing expression of uncoupling protein-1 in brown fat tissue and stimulating the sympathetic nervous system (Dam et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation